Salbutamol Usage Pattern in Asthma Patients at Merdeka Public Health Center Palembang for the Period of January 1 – December 31, 2023 - Mudzakky, Muhammad Yusuf; Adenina, Syarinta; Harahap, Debby Handayati (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Salbutamol is a bronchodilator commonly used in the management of asthma, both in acute and chronic cases. As part of the Short-Acting Beta-2 Agonist (SABA) class, salbutamol is effective in relieving bronchospasms. The purpose of this study was to determine the rationality of drug use at the Merdeka Community Health Center Palembang. A drug utilization study was conducted at Merdeka Public Health Center Palembang in 2024. 96 patients meeting inclusion criteria. Drug use patterns were evaluated for dose rationalization, duration, frequency, contraindications, and interactions. Data analysis was performed using univariate methods. Sociodemographic characteristics showed that women were more prevalent than men (58.3%), with the most common age groups being pre-elderly and elderly (each 36.5%). All salbutamol doses (2–4 mg per administration) were appropriate (100%), with a duration of ≤3 days for all patients. The frequency of salbutamol administration of 3–4 times daily was found in 51% of cases, in line with recommendations. A total of 74% of patients received salbutamol with appropriate consideration of contraindications, while 26% received it despite contraindications, such as hypertension or hypertensive heart disease. Drug interactions were absent in 67.7% of cases, while antagonistic interactions, primarily with amlodipine, occurred in 17.3% of cases. The use of salbutamol at Merdeka Public Health Center Palembang mostly rational to drug use guidelines. However, attention is needed for contraindications and antagonistic interactions, especially with antihypertensive drugs. These findings can serve as a reference for improving asthma management and patient safety.